Lemon Juice Mediated Reaction under Ultrasound Irradiation: Synthesis of Indolofuroquinoxalines as Potential Anticancer Agents - Prasanna, Gutta L.; Rao, Bodapati V. D.; Reddy, Alugubelli Gopi; Rao, Mandava V. Basaveswara; Pal, Manojit (Mini Reviews in Medicinal Chemistry, 2019)
Background: A non-hazardous synthetic methodology has been developed for the preparation of compounds based on indolofuroquinoxaline framework. Lemon juice that is known to play the role of a biocatalyst in various organic reactions was used for this purpose. Method: A number of indolofuroquinoxaline derivatives were prepared via the lemon juice mediated condensation of methyl 2-(2-chloro-1H-indol-3-yl)-2-oxoacetate or its N-alkyl derivatives with 1,2- diamines under ultrasound irradiation. All the synthesized compounds were screened via an MTT assay for their potential anticancer properties in vitro using a number of cancer cell lines including MDA-MB 231, and MCF7, K562, Colo-205 and IMR-32 and the non-cancerous HEK293 cell line. Compounds 3a, 3b and 3c showed promising growth inhibition against K562, MDA-MB 231 and MCF7 cell lines but no significant effects on HEK293 cell line suggesting their selectivity towards cancer cells. Results and Conclusion: Moreover, according to their IC50 values, all these compounds appeared to be relatively more potent towards K562 cell line over MDA-MB 231 and MCF7 cell lines indicating their potential against leukemia.
Keywords: Lemon juice